2014
DOI: 10.2355/isijinternational.54.2461
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Coke from Hydrothermally Treated Biomass in Sequence of Hot Briquetting and Carbonization

Abstract: A sequence of briquetting of biomass solids (bamboo, larch and mallee) at temperature and mechanical pressure of respectively, and carbonization at 900°C produces coke with tensile strength (TS) of 5-19 MPa. Introduction of heat treatment in hot-compressed water (i.e., hydrothermal treatment; HT) of the biomass prior to the briquetting increases TS up to 44, 57 and 42 MPa for the bamboo, larch and mallee, respectively. TS of coke is correlated well and positively with the coke/briquette bulk density ratio, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Even an increase to 5 wt.% charcoal addition in the biocoke could have a beneficial impact in CO 2 emissions by reducing the thermal reserve zone temperature of the blast furnace that leads to a reduction in coke rate. Other researchers [15] have also suggested that hydrothermal carbonization (also termed as hydrous pyrolysis) of biomass can produce residues with properties similar to those of cokes obtained from coal, basing this assumption on the tensile strength of the residues at ambient temperature. However, none of these studies take into consideration the hot mechanical strength of the biocoke, which is one of the main criteria in order to establish the suitability of the biocoke for industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Even an increase to 5 wt.% charcoal addition in the biocoke could have a beneficial impact in CO 2 emissions by reducing the thermal reserve zone temperature of the blast furnace that leads to a reduction in coke rate. Other researchers [15] have also suggested that hydrothermal carbonization (also termed as hydrous pyrolysis) of biomass can produce residues with properties similar to those of cokes obtained from coal, basing this assumption on the tensile strength of the residues at ambient temperature. However, none of these studies take into consideration the hot mechanical strength of the biocoke, which is one of the main criteria in order to establish the suitability of the biocoke for industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also incorporated carbon-containing waste 20) and biomass 21,22) in coke production by briquetting. Kudo et al 23) suggested that high-strength coke can be produced from wooden materials such as bamboo by heating during the compression step. Further, ferro-coke (formed coke containing iron) [24][25][26] is expected to improve reactivity in the blast furnace because iron catalyzes the Boudouard reaction, thereby generating CO gas and reducing the iron ore at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Torrefaction and hydrothermal carbonization (HTC) have been studied for its use in combustion and in the preparation of carbonaceous materials but there are hardly any published works related to its use in the steel industry. There are some studies on the direct addition of charcoal [3,4] but the use of pre-treated biomass in the form of briquettes is very limited [5]. Bituminous binders commonly used to make briquettes generate emissions of polyaromatic hydrocarbons (PAHs) [6].…”
Section: Introductionmentioning
confidence: 99%